New teachers in school organizations. (Journal of Parents and Teachers, 2014)
When a new teacher lands in a school, he has a number of concerns and difficulties that his classmates must take into account. The article presents some of the questions that this new teacher poses and the way in which they should make their entrance in the school.
Keywords: New teacher; school; doubts; difficulties.